Regioselective Reduction of Nitro Ketones by Rhizopus arrhizus - R. SALOKHE, PRABHA; S. SALUNKHE, RAJESHRI (Asian Journal of Chemistry, 2010)
Biocatalytic regioselective reduction of 2-, 3-, 4-nitro acetophenone, 3-nitro-4-methyl acetophenone and 3-nitro propiophenone was accomplished using Rhizopus arrhizus NCIM 878 to yield corresponding (S) -nitro alcohols in good yield and ee (70-87 %). Here we report, Rhizopus arrhizus has a great potential to bring selective reduction of carbonyl group of nitro ketones. However, the biotransformation is very sensitive to the effect of substituent group along with the position of nitro group and steric effect.